A Meta-Analisis of Correlation between Diarrhea and Stunting in Children Under Five - Reza Ramadhana Tahta Firmansyah; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, 2023)
Background: Diarrhea is an infectious disease that can cause children to experience appetite disturbances, resulting in reduced nutritional intake, while the nutrients consumed also fail to be properly absorbed by the body. If this condition is not balanced with appropriate food intake, it can have an impact on cognitive development disorders and height growth, namely stunting. This study aimed to determine whether there was a relationship between a history of diarrhea and the incidence of stunting in toddlers, through a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This study was conducted using a systematic review and meta-analysis with PICO namely, Population: under five, Intervention; diarrhea, comparison: no diarrhea, outcome: stunting. By searching for articles in 2 databases, namely PubMed and Google Scholar, which were published from 2017 to 2022, following keywords